Produção de biossurfactante por Bacilllus licheniformis - Silva, Marcelo de Andrade (2011)
The production of protease and biosurfactant by Bacillus licheniformis UCP-1014 was investigated in this work. The experiments were performed in Erlenmeyer flasks, in triplicate, and inoculum 10% v/v, 150 rpm and 37ºC. A factorial design was conducted to investigate the concentrations of the medium. Metabolic fluid samples were collected, centrifuged and the supernatant used to determine pH, proteolytic activity and surface tension. The liquid was concentrated by ultrafiltration metabolic the stability and proteolytic activity in the retentate was determined for pH and temperature. In making the retentate was used a factorial design, and protease stability was determined during 10, 20 and 30 days at 28ºC. The determination of protease was performed in the presence of azo-casein. The culture of B.licheniformis UCP-1014 produced 112 U/mL protease in the presence of 1% molasses and urea 0,5%, pH 7,5 at 24h of culture. The reduction in surface tension was not significant in these metabolic conditions. The concentration of proteases produced by B. licheniformis UCP-1014 had the highest stability of enzyme activity in the absence of substrate at pH 7 during 60 min of incubation and maximum thermal stability between 40 90ºC for 90 min. The liquid concentrate and formulated metabolic retained about 50% of proteolytic activity whose value decreased during storage at 28ºC. Proteases produced by B. licheniformis UCP-1014 in the presence of nutrients of low cost can be competitive in the market